Badania nad attycką ceramiką geometryczną i jej dekoracją jako sztuką: uwagi o minionych i aktualnych podejściach - Bugaj, Ewa (Folia Praehistorica Posnaniensia, 2024)
In the article, the author attempts to assess the validity of including Attic Geometric pottery and its figural decoration in the category of art and considers the problems of studying art in archaeology in the context of the transformations of cultural concepts concerning archaic man visual experience. Subsequently, in the paper a whole range of art analysis methods that were used in the study of Attic Geometric pottery and its figural ornamentation were presented, taking into account traditional works, as well as new ones based on social constructivism and postmodernity, focussing especially on the original achievements of Polish researchers in this regard and the author own approach.